Design of an embedded communication framework for an amergency telecardiology system - Yıldırım, Onur. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2006., 2006)
Acute myocardial infarction (AMI or MI) occurs whwn a part of the heart muscle dies because of sudden total interruption of blood flow to that area. Itis a life-threatening medical emergency which demands immediate activation of the emergency medical services. This thesis proposes the development of an embedded communication framework designed to enable quick diagnosis of AMI and immediate activation of emergency medical services targeted to it. The system consists of an embedded communication software along with a TCP/IP based sever software for a GSM based ambulatory ECG device. Both, the software components running on the ECG device and the communication server enable the device to be remotely interfaced by the call center software and controlled by the cardiologists.|Keywords: Mobile ECG device, AMI, Pre-hospital thrombolysis, 12-lead ECG over GSM
Keywords: Electrocardiographs.; Myocardial infarction.; Thrombolytic therapy.